Feeding and management strategies to enhance sow and litter performance - Spinler, Mikayla Sue (My University, 2025)
A series of three experiments were conducted to evaluate the effect of precision feeding lactating sows on sow and litter performance, as described in chapter 1 and 2. In each experiment, sows were offered a high Lys diet (control), or a blend of a low and high Lys diet to target a specific Lys intake based on sow BW, parity, and litter size. In Exp. 1, Lys requirements were based on the NRC and INRA models. Sows fed the NRC and INRA treatment curves had lower Lys intake and litter growth performance compared to sows fed a high Lys diet, with no differences in sow body weight (BW) change over lactation. However, litters from sows fed the NRC treatment curve had higher litter performance compared to the INRA treatment curve. In Exp. 2, the NRC estimated Lys requirements were increased by 20% and similar litter performance was achieved when sows received a blend of the low and high Lys diet compared to the control fed sows receiving the high Lys diet, with no differences in sow BW change. Based on the results of these two experiments, a third experiment was conducted under commercial conditions. Similar to Exp. 2, sow Lys intake targets were based on the NRC model + 20%. Blend fed sows consumed less Lys than targeted due to lower ADFI than predicted, resulting in reduced litter performance compared to control fed sows. However, blend fed sows that met their target Lys intake had similar litter performance compared to control fed sows. Chapter 3 determined the effects of two split suckling protocols on litter growth performance and mortality pre- and postweaning compared to no split suckling. Three treatments were evaluated: no split suckling (control), or one of two split suckle protocols: split suckling by birth order or body weight. Overall, the split suckling protocols evaluated in this study did not influence pig growth performance or mortality during the pre- or postweaning periods compared to no split suckling. Chapter 4 evaluated the effect of sow lactation average daily feed intake (ADFI) on litter average daily gain (ADG) and sow BW change over lactation. Lactation ADFI for primiparous and multiparous sows were broken down into five feed intake categories with, 20% of the sows represented in each category. A regression equation was developed to predict litter ADG and sow BW change over change. The analysis indicates that litter ADG is influenced by sow BW loss and lactation feed intake. Results of the regression equations suggest that in primiparous sows, increases in ADFI were associated with a greater improvement in litter ADG compared to multiparous sows, whereas in multiparous sows, ADFI had a stronger effect in reducing BW loss over lactation compared to primiparous sows. Chapter 5 outlines changes in the nutritional values of corn dried distillers grains with solubles (DDGS) and the development of a tool to determine the most economical feeding levels for grow-finish pigs. Changes in ethanol manufacturing practices have reduced the oil and starch content of DDGS, resulting in lower NE values for DDGS than observed in the past. Recent studies evaluating low-oil DDGS in finishing pig diets have observed decreased growth performance compared with past studies with high-oil DDGS. To support the decision-making process, a tool was developed to help producers determine the most economical levels of DDGS in finishing pig diets, factoring in feed cost savings and income over feed cost on both live and carcass weight basis with varying DDGS oil content.
Keywords: Growth performance; Lactation; Precision feeding; Surviability